Analisis Penyebaran Informasi di Perpustakaan Dalam Memanfaatkan Media Sosial - Kartini Kartini; Restiana Restiana; Putri Lestari; Rahima Husna (Dakwatussifa: Journal of Da'wah and Communication, 2023)
The use of social media has now become a way of life. Libraries as institutions providing information services must be able to adapt to this. Currently there are many libraries that use social media, but not many libraries can make optimal use of social media. This study aims to determine the benefits of social media as a medium for disseminating library information, trends in the use of social media in libraries, what social media platforms can be used in libraries and how to optimize the use of social media for libraries. In this study the authors used qualitative methods. The data collection technique is to do a document review or literature review. Optimum use of social media can support libraries in providing the best service to users. Therefore, with the current technological developments, the library must be able to take advantage of the opportunity as well as possible to maintain the existence of the library. Keywords: Trends; Social media; Library.